2018
DOI: 10.1007/s10068-018-0513-z
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of polysaccharides under vacuum condition from Lentinus edodes stipe and their antioxidant activities in vitro

Abstract: To improve the efficiency of polysaccharide extraction, vacuum technology was used to breakdown the cell wall to extract polysaccharides from Lentinus edodes stipe, and the optimal parameters were optimized by response surface methodology. Then the antioxidant activities in vitro of the polysaccharides were evaluated. Results showed that the optimal conditions for polysaccharide extraction were temperature of 62°C, vacuum of 0.08 MPa, stirring speed of 1200 r/min, time of 25 min and material/liquid ratio of 1:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…The control always presented the lowest antioxidant capacity. Corroborating the results presented here, previous studies demonstrated that the polysaccharides from LES had been proved to have the DPPH and ABTS radical scavenging rate reached 43.58% and more than 90% when the concentration was 2 mg/mL (Li et al, 2019).…”
Section: Antioxidant Assayssupporting
confidence: 88%
“…The control always presented the lowest antioxidant capacity. Corroborating the results presented here, previous studies demonstrated that the polysaccharides from LES had been proved to have the DPPH and ABTS radical scavenging rate reached 43.58% and more than 90% when the concentration was 2 mg/mL (Li et al, 2019).…”
Section: Antioxidant Assayssupporting
confidence: 88%
“…A substantial cavitation effect caused by the generation of microbubbles during vacuum extraction enhances the solubility of biological components in the solvent medium and enables rapid extraction at low temperatures. By optimizing the conditions including 0.08 MPa of pressure, 62 °C of extraction temperature, 25 min of extraction time, and 26 mL/g of liquid–solid ratio, the maximum yield of polysaccharides reached 4.28% [ 82 ]. As for nanoparticle-assisted extraction, insoluble tungsten carbide nanoparticle powder was used for a nanoknife to extract β-glucan from Sparassis crispa and Pellinus linteus [ 83 ].…”
Section: Extraction Methods Of Efpsmentioning
confidence: 99%
“…The ideal extraction parameters were: vacuum degree of 0.08 MPa, solid to liquid ratio of 1:26, temperature of 65 ℃, extraction duration of 25 min, and stirring speed of 1200 r/min. The polysaccharide extraction rate was 4.28% (Li et al 2019). Besides the aforementioned auxiliary extraction methods, polysaccharides could also be extracted using ultrasonic subcritical water conditions (190 W, 140 °C), achieving an extraction rate of 17.34% for Lentinan (Zhang et al 2018).…”
Section: Supercriticalmentioning
confidence: 99%